Revitalizing Morality Through Play: A Study on the Integration of Traditional Games at RA Al Anbiya - Azzahra, Arwa; Nur, Lutfi; Purwati, Purwati (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Traditional games not only hold rich cultural values but also serve as an effective learning medium to instill moral values in early childhood. This research aims to identify how the integration of traditional games in learning at RA Al Anbiya can help bring children's morals to life. The research method used is descriptive qualitative, with a case study approach. Data were collected through observation, in-depth interviews, and documentation. The results showed that traditional games such as cranklek, congklak, and gobak sodor are able to encourage the development of moral values such as honesty, responsibility, cooperation, and respect. Teachers at RA Al Anbiya play an important role in designing traditional game-based learning, ensuring that each game is linked to the learning of moral values. In addition, parental involvement is also a supporting factor in the success of this integration. This research confirms that traditional games are not just a source of entertainment but also an effective tool for shaping children's character. Thus, the integration of traditional games in early childhood education institutions can be an innovative strategy to support holistic moral education.